PENGARUH CAPITAL INTENSITY, BEBAN IKLAN, DAN KOMPENSASI RUGI FISKAL TERHADAP PENGHINDARAN PAJAK - Ramadhanti Dwi Lestari (2022)
The purpose of this study was to determine the effect of capital intensity, advertising expense and fiscal loss compensation on tax avoidance. This research is quantitative research. The data used in this study is secondary data obtained from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The sampling technique used was purposive sampling. The sample in this study used 61 manufacturing companies with 3 years of research so that a total sample of 183 was obtained. The analytical method used was panel data regression analysis. Based on the results of data analysis, it can be concluded that (1) capital intensity has no significant effect on tax avoidance, (2) advertising expense has no significant effect on tax avoidance, (3) fiscal loss compensation has no significant effect on tax avoidance.